EFEKTIVITAS PELAKSANAAN WEWENANG JAKSA SEBAGAI PENGACARA NEGARA DALAM KASUS KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DI INDONESIA - Rahardhini, Halida (Universitas Wiralodra, 2024)
The authority of the prosecutor as an applicant in bankruptcy cases and postponement of debt payment obligations has been regulated in Article 2 of Law Number 37 of 2004 concerning Insolvency and Postponement of Debt Payment Obligations, this is related to the need for settlement of insolvency cases related to the public interest as a limitation. Asis known that in the current insolvency case, many of the victims are also the community as parties involved in the company that will be declared bankrupt. However, the problem is that until now there are only 2 bankruptcy cases related to the public interest that use prosecutors as applicants. Based on these issues, the author intends to discuss the extent of the effectiveness of the prosecutor's authority as a state attorney in bankruptcy cases and the postponement of debt repayment obligations in Indonesia. The writing of this journal uses the normative juridical method, which uses secondary data in conducting the analysis. Based on the results of the author's analysis, that in the position of the prosecutor as the authorized state attorney as an applicant in bankruptcy cases and delays in debt payment obligations has been explained and regulated in the relevant laws and regulations in Indonesia, but in its implementation there are several obstacles that occur both internally in the prosecutor's office and from external factors such as the definition of public interest which has not been clearly regulated in the laws and regulations in Indonesia has not been widely implemented to understand the authority of prosecutors as applicants in insolvency cases in the public interest.